2005
DOI: 10.1021/jf051656k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphate and Copper on Reductive Dechlorination of Thiobencarb in California Rice Field Soils

Abstract: The potential for reductive dechlorination of the herbicide thiobencarb (TB) by microbes and its prevention in saturated anaerobic rice field soils was examined in laboratory microcosms. TB is effective in controlling both annual grasses and broadleaf weeds. In anoxic microcosms, TB was effectively degraded within 30 days to its dechlorinated product, deschlorothiobencarb (DTB), in two Sacramento Valley rice field soils. TB dechlorination, and subsequent degradation, followed pseudo-zero- (lag phase) and first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Some clomazone degradation and compound 2 formation were observed in anaerobic samples after 19 days, possibly due to the stimulation of spores resistant to autoclaving, which has been previously documented in rice field soil , . To illustrate the potential impact this may have on first-order kinetic calculations, two regression lines are plotted in Figure : clomazone degradation through (A) 19 days (no observed parent degradation) and (B) 38 days (equilibrium time).…”
Section: Discussionmentioning
confidence: 90%
“…Some clomazone degradation and compound 2 formation were observed in anaerobic samples after 19 days, possibly due to the stimulation of spores resistant to autoclaving, which has been previously documented in rice field soil , . To illustrate the potential impact this may have on first-order kinetic calculations, two regression lines are plotted in Figure : clomazone degradation through (A) 19 days (no observed parent degradation) and (B) 38 days (equilibrium time).…”
Section: Discussionmentioning
confidence: 90%
“…A pilot study, where soil was subjected to (a) triple autoclaving, (b) microwave irradiation and (c) sodium azide amendment, revealed that autoclaving was the most effective inhibiter of clomazone degradation, while the other two methods had little effect (data not shown). Two previous studies6, 16 found anaerobic spore rejuvenation in autoclaved flooded soil microcosms to cause degradation of clomazone and thiobencarb, which confounded the controlling effects of sterilization. However, the former found autoclaving to be effective over 28 days, which is twice the length of the regulatory rice field water holding time in the Sacramento Valley, and is sufficient time to test whether the compound will degrade significantly via photolysis while the fields are flooded.…”
Section: Introductionmentioning
confidence: 98%
“…Since most clomazone-C under both soil conditions was recovered in DOC or respired CO 2 , and not in PLFA, this suggests the compound is degraded by cometabolic processes. As with thiobencarb, another popular chloroaromatic herbicide, amendment with organic carbon, phosphate, and copper are expected to alter the dynamics of clomazone biodegradation.…”
Section: Discussionmentioning
confidence: 99%